(Bad) Feelings about Meeting Them? Episodic and Chronic Intergroup Emotions Associated with Positive and Negative Intergroup Contact As Predictors of Intergroup Behavior - Kauff, Mathias; Asbrock, Frank; Wagner, Ulrich; Pettigrew, Thomas F.; Hewstone, Miles; Schäfer, Sarina J.; Christ, Oliver (Frontiers in Psychology, 2017)
Based on two cross-sectional probability samples (Study 1: N = 1,382, Study 2: N = 1,587), we studied the interplay between positive and negative intergroup contact, different types of intergroup emotions (i.e., episodic intergroup emotions encountered during contact and more general chronic intergroup emotions), and outgroup behavior in the context of intergroup relations between non-immigrant Germans and foreigners living in Germany. In Study 1, we showed that positive and negative contact are related to specific episodic intergroup emotions (i.e., anger, fear and happiness). Results of Study 2 indicate an indirect effect of episodic intergroup emotions encountered during contact experiences on specific behavioral tendencies directed at outgroup members via more chronic situation-independent intergroup emotions. As expected, anger predicted approaching (discriminatory) behavioral tendencies (i.e., aggression) while fear predicted avoidance. The results extend the existing literature on intergroup contact and emotions by addressing positive and negative contact simultaneously and differentiating between situation-specific episodic and chronic intergroup emotions in predicting discriminatory behavioral tendencies.